THE IMPACT OF CASH CONVERSION CYCLE ON FINANCIAL DISTRESS WITH PROFITABILITY AS A MODERATING VARIABLE - Fitratul Firda Amaliah; Arif Darmawan (Pusat P2M Politeknik Negeri Batam, 2019)
This study aims to provide empirical evidence on the impact of profitability on the correlation cash conversion cycle to financial distress. The population in this study is a manufacturing company listed on the Indonesia Stock Exchange period 2010 to 2016 with a total sample of 9 companies. The sample collection method using purposive sampling and the testing measurement used was regression analysis. The result of this study proves that the cash conversion cycle affect positive to financial distress and profitability able to moderate the relationship between the cash conversion cycle to financial distress.